SEKILAS TENTANG MANIK-MANIK KEMILING, PUNGGUNGHARDJO, LAMPUNG TENGAH - Rita Istari (Berkala Arkeologi, 1996)
In this paper, the study will focus on the presence of beads, particularly those found in one of the mounds of land in Dukuh Kemiling, Punggungharjo Village. The number of bead finds and bead candidates on this site is interesting to study, in addition, bricks with the date 1325 AD were also found. The data found at the Kemiling site are very interesting because they are the first findings in Indonesia based on the number of beads and context which is thought to be a sacred place in the past. In this regard, this study is intended to reconstruct the role and function of beads, that these remains are not only used as grave provisions or for aesthetic purposes, but also related to the function of rituals.